2015
DOI: 10.1116/1.4929833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defect density on ultrathin graphene-based metal diffusion barriers

Abstract: The authors investigated the effects of defect density on the performance of monolayer graphene as a barrier to metal diffusion. The defects were introduced to the graphene by controlled ultraviolet-ozone irradiation. The barrier performance of pristine graphene was found to be superior to that of defective graphene at temperatures up to 700 °C. Changes in surface morphology were more prevalent in the defective graphene-based films than in the pristine graphene-based film; the thermal stability of graphene fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…These data may also indicate that minimizing the graphene defect density is important for reducing oxidation of Ge and that oxidation of Ge preferentially occurs at defects in graphene, similar to previous results for graphene on metal surfaces. For example, the reduction in oxidation of Ge(001) and Ge(111) with increasing H 2 :CH 4 (Figure ) directly correlates with a decrease in the total defect density in graphene (Figures –). Moreover, at least for the growth conditions used here, these results indicate that atomic-scale defects contribute to oxidation of Ge to a much greater extent than the relatively sparse pinhole defects, as oxidation of Ge is reduced by increasing the H 2 :CH 4 ratio (Figure ) despite an increase in ρ pinhole (Figure ).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…These data may also indicate that minimizing the graphene defect density is important for reducing oxidation of Ge and that oxidation of Ge preferentially occurs at defects in graphene, similar to previous results for graphene on metal surfaces. For example, the reduction in oxidation of Ge(001) and Ge(111) with increasing H 2 :CH 4 (Figure ) directly correlates with a decrease in the total defect density in graphene (Figures –). Moreover, at least for the growth conditions used here, these results indicate that atomic-scale defects contribute to oxidation of Ge to a much greater extent than the relatively sparse pinhole defects, as oxidation of Ge is reduced by increasing the H 2 :CH 4 ratio (Figure ) despite an increase in ρ pinhole (Figure ).…”
Section: Resultssupporting
confidence: 85%
“…Figure indicates that passivation of Ge by graphene can be enhanced by growing graphene with a high H 2 :CH 4 ratio, and thus low growth rate, and that passivation is most effective on Ge(110). It has been shown that oxidation of metal surfaces preferentially occurs at defects in graphene and critically depends on the graphene/substrate interaction strength . We therefore hypothesize that the oxidation behavior in Figure can be explained by the effect of H 2 :CH 4 and Ge surface orientation on the (1) density of pinhole defects in graphene, (2) density of atomic-scale defects in graphene, (3) graphene/Ge interaction strength, or (4) degradation of graphene after exposure to air.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The use of nonnative substrates often requires post-synthesis graphene layer transfers, which can damage the graphene and create tears, wrinkles, and point defects. The impacts of this transfer process on effectiveness as a diffusion barrier have not been quantified, although the impacts of other intentional defects have been studied [9].…”
mentioning
confidence: 99%